Reconstruction of Sickle Cell Disease with Circulating Sickling Red Blood Cells in Novel Humanized Cytokines and Liver Mistrg Mice - Song, Yuanbin; Gbyli, Rana; Shan, Liang; Liu, Wei; Gao, Yimeng; Patel, Amisha; Fu, Xiaoying; Wang, Xiaman; Xu, Mina L.; Qin, Ashley; Bruscia, Emanuela; Tebaldi, Toma; et al. (Blood, 2020)
In vivo models of human erythropoiesis with generation of circulating mature human red blood cells (huRBC) have remained elusive, limiting studies of primary human red cell disorders. In our prior study, we have generated the first combined cytokine-liver humanized immunodeficient mouse model (huHepMISTRG-Fah) with fully mature, circulating huRBC when engrafted with human CD34+ hematopoietic stem and progenitor cells (HSPCs)1. Here we present for the first time a humanized mouse model of human sickle cell disease (SCD) which replicates the hallmark pathophysiologic finding of vaso-occlusion in mice engrafted with primary patient-derived SCD HSPCs. SCD is an inherited blood disorder caused by a single point mutation in the beta-globin gene. Murine models of SCD exclusively express human globins in mouse red blood cells in the background of murine globin knockouts2 which exclusively contain murine erythropoiesis and red cells and thus fail to capture the heterogeneity encountered in patients. To determine whether enhanced erythropoiesis and most importantly circulating huRBC in engrafted huHepMISTRG-Fah mice would be sufficient to replicate the pathophysiology of SCD, we engrafted it with adult SCD BM CD34+ cells as well as age-matched control BM CD34+ cells. Overall huCD45+ and erythroid engraftment in BM (Fig. a, b) and PB (Fig. c, d) were similar between control or SCD. Using multispectral imaging flow cytometry, we observed sickling huRBCs (7-11 sickling huRBCs/ 100 huRBCs) in the PB of SCD (Fig. e) but not in control CD34+ (Fig. f) engrafted mice. To determine whether circulating huRBC would result in vaso-occlusion and associated findings in SCD engrafted huHepMISTRG-Fah mice, we evaluated histological sections of lung, liver, spleen, and kidney from control and SCD CD34+ engrafted mice. SCD CD34+ engrafted mice lungs showed an increase in alveolar macrophages (arrowheads) associated with alveolar hemorrhage and thrombosis (arrows) but not observed control engrafted mice (Fig. g). Spleens of SCD engrafted mice showed erythroid precursor expansion, sickled erythrocytes in the sinusoids (arrowheads), and vascular occlusion and thrombosis (arrows) (Fig. h). Liver architecture was disrupted in SCD engrafted mice with RBCs in sinusoids and microvascular thromboses (Fig. i). Congestion of capillary loops and peritubular capillaries and glomeruli engorged with sickled RBCs was evident in kidneys (Fig. j) of SCD but not control CD34+ engrafted mice. SCD is characterized by ineffective erythropoiesis due to structural abnormalities in erythroid precursors3. As a functional structural unit, erythroblastic islands (EBIs) represent a specialized niche for erythropoiesis, where a central macrophage is surrounded by developing erythroblasts of varying differentiation states4. In our study, both SCD (Fig. k) and control (Fig. l) CD34+ engrafted mice exhibited EBIs with huCD169+ huCD14+ central macrophages surrounded by varying stages of huCD235a+ erythroid progenitors, including enucleated huRBCs (arrows). This implies that huHepMISTRG-Fah mice have the capability to generate human EBIs in vivo and thus represent a valuable tool to not only study the effects of mature RBC but also to elucidate mechanisms of ineffective erythropoiesis in SCD and other red cell disorders. In conclusion, we successfully engrafted adult SCD patient BM derived CD34+ cells in huHepMISTRG-Fah mice and detected circulating, sickling huRBCs in the mouse PB. We observed pathological changes in the lung, spleen, liver and kidney, which are comparable to what is seen in the established SCD mouse models and in patients. In addition, huHepMISTRG-Fah mice offer the opportunity to study the role of the central macrophage in human erythropoiesis in health and disease in an immunologically advantageous context. This novel mouse model could therefore serve to open novel avenues for therapeutic advances in SCD. Reference 1. Song Y, Shan L, Gybli R, et. al. In Vivo reconstruction of Human Erythropoiesis with Circulating Mature Human RBCs in Humanized Liver Mistrg Mice. Blood. 2019;134:338. 2. Ryan TM, Ciavatta DJ, Townes TM. Knockout-transgenic mouse model of sickle cell disease. Science. 1997;278(5339):873-876. 3. Blouin MJ, De Paepe ME, Trudel M. Altered hematopoiesis in murine sickle cell disease. Blood. 1999;94(4):1451-1459. 4. Manwani D, Bieker JJ. The erythroblastic island. Curr Top Dev Biol. 2008;82:23-53. [Display omitted] Xu:Seattle Genetics: Membership on an entity's Board of Directors or advisory committees. Flavell:Zai labs: Consultancy; GSK: Consultancy.